NAFLD: Diagnostic Algorithms for Regulating Patient Fluxes - Pallini, Giada; Tsochatzis, Emmanuel A. (Current Pharmaceutical Design, 2021)
The global prevalence of NAFLD is estimated to be over 25% and it is already the leading cause of chronic liver disease in industrialized countries, as a consequence of the spread of obesity and metabolic syndrome. The prognosis of NAFLD is generally benign in the absence of fibrosis, but liver fibrosis rapidly progresses in 20% of the cases and can lead to cirrhosis and/or HCC. This review focuses on non-invasive fibrosis testing strategies for patients with NAFLD in order to increase the efficiency and effectiveness of diagnosis and care, regulating secondary care referral fluxes. An integrated management plan between primary care and secondary care with a defined algorithm of non-invasive testing to stratify the risk of NAFLD fibrosis is indispensable to increase the early diagnosis of fibrosis but also decrease unnecessary referrals.
Keywords: ELF